Determination of the most prevalent reasons for requesting drugs without prescription in Kerman pharmacies - MR Heidari (Babol University of Medical Sciences, 1999)
Objective: Consumption of drugs without prescriptions arises many problems. In this study the most prevalent reasons for requesting drugs without prescriptions were determined. Methods: This study was performed by a descriptive profile complete for 300 people from the pharmacies in Kerman province. Findings: The answer to the first question of profile “Why do you want a drug without prescription?”, are: I have used this drug before, it was effective, I have the same disease now and I want to buy the same drug in 51% of cases, “I can’t afford the doctor’s visit” in 20.6%, I know what the doctor will prescribe me and I don’t want to pay the doctor in 8.3%, I am a doctor for me in 4.7%, the stence of open markets for drugs in 3.6%, “The doctor will prescribe and drug I ask him to”, in 2.3%, “I am very sick, and I can’t go to the doctor” in 2%, “I am a traveler” in 2%, “Without prescription is easier” in 1.7%, “The pharmacies do not dispense all the prescribed drug by the physician” in 1.7%, “I haven’t brought the prescription” in 0.7% and “What ever the doctor prescribes, the pharmacies give the similar one”, in 0.7% of cases. The frequency of answers to the second question “Why don’t you consult with a doctor are”: “I can’t afford the prescription fees” in 32.4% of cases, “I don’t have time to go to a doctor” in 23.7%, “I know what the doctor prescribes me and so I don’t want to pay the doctor” in 15.7%, “My family doctor has gone on trip” in 6.7%, “It is difficult to consult good doctor because they are busy” in 6.7%, “I am ill in bed and I can’t a doctor” in 5%, “I am a doctor for me” in 4%, “The doctor will prescribe me whatever I ask” in 3%, “I have taken this drug before, it was effective I have the same illness” in 1.6%, “It is more comfortable and easier without prescription” in 1.3% and “Whatever the doctor prescribes the pharmacies give the similar ones” in 0.6% of cases. Conclusion: Based on these results, it is necessary to pay more attention to the various reasons of requesting drug without prescription.